2022
DOI: 10.1002/anie.202203564
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry in Magnetic Fields

Abstract: Developing new strategies to advance the fundamental understanding of electrochemistry is crucial to mitigating multiple contemporary technological challenges. In this regard, magnetoelectrochemistry offers many strategic advantages in controlling and understanding electrochemical reactions that might be tricky to regulate in conventional electrochemical fields. However, the topic is highly interdisciplinary, combining concepts from electrochemistry, hydrodynamics, and magnetism with experimental outcomes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 142 publications
1
119
1
1
Order By: Relevance
“…Employing their previously 164 developed method for the ortho selective borylation of anisole with a yttrium catalyst, Xu and co-workers recently reported a strategy for the selective C2 borylation of pyridine derivatives (Scheme 56). 165 The authors demonstrated that a large number of substrates underwent selective C2 borylation, which can be further converted into their hydroxy derivatives using oxone as the oxidising agent. The mechanistic investigations revealed that the reaction proceeded via C–H activation as the rate-determining step.…”
Section: Directed Ortho C–h Borylationmentioning
confidence: 99%
“…Employing their previously 164 developed method for the ortho selective borylation of anisole with a yttrium catalyst, Xu and co-workers recently reported a strategy for the selective C2 borylation of pyridine derivatives (Scheme 56). 165 The authors demonstrated that a large number of substrates underwent selective C2 borylation, which can be further converted into their hydroxy derivatives using oxone as the oxidising agent. The mechanistic investigations revealed that the reaction proceeded via C–H activation as the rate-determining step.…”
Section: Directed Ortho C–h Borylationmentioning
confidence: 99%
“…In addition, since most electrode materials are not ferromagnetic (e.g., platinum, gold, carbon), interferance is unlikely to result in significant noise as eddy currents will not be induced in the absence of a relatively strong and dynamic magnetic field. Magnetoelectrochemistry is a relatively new field which uses strong magnetic fields (e.g., >0.5 T) to influence electrochemical processes such as radical generation and corrosion . However, since magnetic fields are generally weak in the absence of a proximal appliance/source (∼10 μT), the contribution to electrochemical noise may be ignored under typical laboratory conditions.…”
Section: Theorymentioning
confidence: 99%
“…Magnetoelectrochemistry is a relatively new field which uses strong magnetic fields (e.g., >0.5 T) to influence electrochemical processes such as radical generation and corrosion. 23 However, since magnetic fields are generally weak in the absence of a proximal appliance/source (∼10 μT), 24 the contribution to electrochemical noise may be ignored under typical laboratory conditions.…”
Section: Theorymentioning
confidence: 99%
“…Inspired by this observation, very recently, our group explored a catalytic ortho-selective C-H borylation of pyridines with pinacolborane (HBpin) by utilization of an yttrocene catalyst Cp* 2 Y(THF)CH 2 SiMe 3 (Cp* = C 5 Me 5 ), providing facile access to a variety of 2-pyridyl boronates with a broad substrate scope and high atom economy. 26 On the grounds of our prior work in 2019 (Scheme 5), a series of rare-earth metallocene complexes were evaluated for reaction of DMAP with HBpin under catalytic conditions. It was found that the rare-earth metal ionic radius plays a pivotal role in selectivity tuning.…”
Section: Scheme 5 Stoichiometric Ortho-selective C-h Borylation Of Py...mentioning
confidence: 99%